ALLERGIC RHINITIS: EFFICIENT THERAPEUTIC OPPORTUNITIES - M. L. Derbeneva; A. L. Guseva (Медицинский совет, 2018)
The article presents epidemiology, pathogenesis and classification of allergic rhinitis. The highlights of the article include nonpharmacological and pharmacological methods of treatment of this disease, and the efficacy of different groups of drugs for relief and management of allergic rhinitis symptoms.